Links and orbital factors in Al_Damiri’s Book of The Great Animal Life (Journal of the College of Basic Education, 2022)
This research deals with the disclosure of one of the pilgrim’s techniques employed in the book “The Life of the Great Animal” by Al-Damiri, namely (the pilgrim links and factors) due to the abundance of linguistic and grammatical methods that are concerned with the argumentative deliberative lesson, which cannot be left without studying it. In abundance, it is one of the dominant elements of the Damiri text, especially (the condition and the palace). Despite its presence in the deliberative lesson, it is the subject of persuasion, which is the subject of our study of the Book of the Great Animal Life.